Cover Picture: Superacids Based on Pentafluoroorthotellurate Derivatives of Aluminum (Angew. Chem. Int. Ed. 28/2017). Issue 28 (1st June 2017) - Wiesner, Anja; Gries, Thomas W.; Steinhauer, Simon; Beckers, Helmut; Riedel, Sebastian
Abstract : Novel members of the league of extraordinary superacids, namely the Brønsted superacid H[Al(OTeF5 )4 ] and the Lewis superacid "Al(OTeF5 )3 ", have been synthesized starting from AlEt3 and HOTeF5 . In their Communication onpage 8263 ff., S. Riedel and co‐workers describe the preparation and crystallization of five salts of the weakly coordinating anion [Al(OTeF5 )4 ] −, which is shown in the spotlight, through the use of H[Al(OTeF5 )4 ].